Firm Wage Premia, Rent-Sharing and Monopsony When Underemployment is High - Bassier, Ihsaan (Southern Centre for Inequality Studies (SCIS), 2021)
How important are firms in the labour markets of developing countries? Using matched employer-employee data from South Africa, I find firms explain a larger share of wages than in other, richer countries. It shows this can be parsimoniously explained by the high degree of underemployment. Estimating separations elasticities by instrumenting wages of matched workers with firm wages, among other methods, I find a low separations elasticity which generates a high degree of monopsony. The correspondingly high estimated rent-sharing elasticity explains the important role of firm wage policies, even in an economy with a large labour surplus. This paper is a work in progress.
Keywords: Labour markets of developing countries; Rent-sharing elasticity; Firm wage policies; Monopsony; Firm Wage Premia